Understanding the Turbulence of Business Environment in Telecom Industry: Empirical Evidence from Indonesia - Muhammad Imam Nashiruddin (Buletin Pos dan Telekomunikasi, 2018)
Previous studies have shown that business performance is mostly determined by the ability of a company to create competitive advantage. However, the rapid changes in technology, markets, regulations and hypercompetition have made the business environment increasingly uncertain and unpredictable so that it can erode competitive advantage. This phenomenon is known as the turbulence of business environment and can cause a company to have difficulty maintaining its competitive advantage so that it is very interesting to study further. The purpose of this study is to understand how the turbulence of business environment occurs in the telecommunications industry in Indonesia. The study involved 213 leaders of business units of telecommunications operators in Indonesia as research respondents. The research methods used are descriptive survey and explanatory survey using component-based structural modeling, Partial Least Square-Path Modeling (PLS-PM). The results of the study showed that the telecommunications industry in Indonesia has experienced high turbulence of business environment, caused mainly by competitive turbulence. However, it was found that the technological turbulence and the market turbulence have contributed the most dominant to the occurrence of turbulence business environment in telecommunication industry. This study also discussed the problem solving of the business environment turbulence and recommendations for the sustainability of the telecommunications industry in Indonesia.*****Tujuan dari penelitian ini adalah untuk mendapatkan gambaran bagaimana turbulensi lingkungan bisnis yang terjadi pada industri telekomunikasi di Indonesia. Penelitian melibatkan pimpinan unit bisnis penyelenggara telekomunikasi sebagai responden penelitian. Metode penelitian yang digunakan adalah metode descriptive survey dan explanatory survei menggunakan pemodelan struktural berbasis komponen yaitu Partial Least Square-Path Modelling (PLS-PM). Hasil penelitian menunjukkan bahwa industri penyelenggaraan telekomunikasi di Indonesia mengalami gejolak turbulensi lingkungan bisnis yang tinggi, disebabkan terutama oleh turbulensi lingkungan kompetisi. Meskipun demikian, ditemukan bahwa sesungguhnya turbulensi lingkungan teknologi dan turbulensi lingkungan pasar yang berkontribusi paling dominan terhadap terjadinya turbulensi lingkungan bisnis pada industri telekomunikasi. Dalam penelitian ini juga dibahas pemecahan masalah turbulensi lingkungan bisnis tersebut dan rekomendasinya bagi keberlangsungan industri telekomunikasi di Indonesia.